High-voltage fast-charging lithium ion secondary battery
By using the interaction between pyrosulfate boron trifluoride composite lithium salt and a hard carbon negative active material with a specific specific surface area in lithium-ion secondary batteries, the problem of insufficient fast charging performance of lithium-ion secondary batteries under low temperature conditions is solved. , achieving low-impedance channel construction and performance improvement for batteries.
Patent Information
- Application Number
- CN202310883885.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-19
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2043-07-19
AI Technical Summary
The existing lithium-ion secondary batteries have insufficient fast charging performance under low temperature conditions, and the excessive internal impedance leads to decay of battery capacity and reduced safety.
A low-resistance lithium ion migration channel is constructed by using pyrosulfate boron trifluoride composite lithium salt to interact with a hard carbon negative active material with a specific specific surface area.
It significantly improves the fast charging performance and low-temperature performance of lithium-ion secondary batteries, and reduces the diffusion resistance and charge transfer resistance of the battery.
Smart Images

Figure CN119340474A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of lithium ion secondary batteries, and in particular to a high-voltage fast-charge lithium ion secondary battery containing a pyrosulfate boron trifluoride composite lithium salt and a hard carbon negative electrode. Background Art
[0002] At present, the anxiety of recharging new energy vehicles during long-distance travel has become a core issue of concern to car owners. Therefore, the low-temperature fast charging performance of batteries has received more and more attention. The internal impedance of the battery is one of the important criteria for evaluating the fast charging and low-temperature performance of lithium-ion batteries. Excessive internal impedance will cause the battery to produce a large internal polarization during the charging and discharging process, thereby affecting the battery capacity and producing more side reactions under extreme conditions. Once the internal polarization of the battery is large during the rate charging process, it is easy to generate overpotential, resulting in irreversible lithium deposition at the negative electrode, further causing the battery capacity to decay and safety to decrease.
[0003] Electrochemical impedance spectroscopy is a commonly used method to evaluate the internal impedance of batteries. Lu et al. (The timescale identification decoupling complicated kinetic processes in lithium batteries[J]. Joule, 2022, 6(6): 1172-1198.) summarized the method of decoupling electrochemical impedance spectroscopy data using relaxation time distribution function, and roughly divided the sources of battery internal impedance into ohmic impedance (R0), liquid-solid interface impedance (R sei ), charge transfer impedance (R ct ), diffusion impedance (R w ), etc. In different battery systems, the relaxation time (frequency domain) of each type of impedance source is relatively close, so the relaxation time distribution function can be directly used to decouple and distinguish the impedance types. Through electrochemical impedance spectroscopy analysis, it is found that the diffusion impedance dominated by solid-phase diffusion accounts for a large part of the internal impedance of the battery. During the charging and discharging process of the battery, the positive electrode, electrolyte, diaphragm, negative electrode, and the solid phase formed by the reaction of the electrolyte and the negative electrode can be simplified as a series path. Therefore, if the impedance of any component is too high, it is easy to cause the battery to have shortcomings, thereby affecting the fast charging performance and low temperature performance of the battery. Among them, the solid phase composition (SEI film) formed by the reaction of the negative electrode, electrolyte (mainly additives) and the negative electrode has the most critical effect on the internal impedance of the battery.
[0004] Therefore, it is necessary and urgent to propose a solution that can simultaneously solve the problems of excessive solid phase impedance formed by the electrolyte, the negative electrode, and the reaction between the electrolyte and the negative electrode, and apply it to lithium-ion secondary batteries to improve fast charging performance and low-temperature performance. Summary of the invention
[0005] Pyrosulfate boron trifluoride composite lithium salt is a new electrolyte additive developed by the applicant, which can improve the cycle performance, high temperature storage performance and low temperature performance of the battery. Further research found that the pyrosulfate boron trifluoride composite lithium salt has the effect of reducing the liquid-solid interface impedance and charge transfer impedance inside the battery, but when it is used with different negative electrode active materials at the same time, the effect of improving the fast charging performance and low temperature performance of the battery is quite different.
[0006] In order to solve the above technical problems, the present invention proposes a high-voltage fast-charging lithium-ion secondary battery formed by the interaction of pyrosulfate boron trifluoride composite lithium salt and a specific negative electrode active material, which can construct a low-impedance lithium ion migration channel, thereby improving the battery's fast charging performance and low-temperature performance.
[0007] The objective of the present invention is achieved through the following technical solutions:
[0008] A high-voltage fast-charge lithium-ion secondary battery comprises a positive electrode, a negative electrode, a separator and an electrolyte, wherein the electrolyte comprises a main lithium salt, a non-aqueous solvent and an additive, wherein the additive comprises:
[0009] A novel composite lithium salt, wherein the novel composite lithium salt comprises at least a pyrosulfate boron trifluoride composite lithium salt having a structure shown in the following formula (I-1):
[0010]
[0011] The novel composite lithium salt accounts for 0.02-5.0 wt% of the total mass of the electrolyte; preferably 0.1-2.0 wt% of the total mass of the electrolyte;
[0012] Furthermore, the negative electrode comprises:
[0013] An active material capable of reversibly absorbing and releasing lithium ions, wherein the specific surface area of the active material is 0.1 to 20.0 m 2 / g; preferably, the specific surface area of the active substance is 0.5 to 10.0 m 2 / g.
[0014] When the active substance is a single substance, the specific surface area of the single substance must meet the above limitations;
[0015] When the active substances are two or more substances, the specific surface area of any one of the substances must meet the above limitations.
[0016] When the novel composite lithium salt and the negative electrode active material under the above specific surface area coexist, the purpose of constructing a low-impedance, stable and transparent lithium ion migration channel can be achieved, thereby improving the fast charging performance and low-temperature performance of the battery. If the specific surface area of the negative electrode active material is too low, it is easy to cause the path of lithium ions migrating inside the negative electrode active material to become longer, thereby increasing the difficulty of solid-phase diffusion of lithium ions, increasing the battery diffusion impedance and the internal impedance of the battery, and reducing the fast charging performance and low-temperature performance of the battery; if the specific surface area of the negative electrode active material is too high, it is easy to cause too much electrolyte to participate in the formation process of the liquid-solid interface phase, which increases the side reactions, increases the number of irreversible lithium ions, thickens the interface phase, increases the internal impedance of the battery, and reduces the fast charging performance and low-temperature performance of the battery.
[0017] The active material of the negative electrode is selected from carbon materials and / or silicon materials; the carbon material is selected from at least one of natural graphite, artificial graphite, and hard carbon, and the silicon material is selected from silicon and / or silicon monoxide.
[0018] The specific types of carbon materials described in the present invention are commonly used materials in the field of secondary batteries. Among them, natural graphite refers to graphite materials with inconsistent particle diameters or a wide distribution of particle diameters. Generally, there are defects on its surface. The lithium-ion secondary batteries prepared using it generally have more side reactions and relatively poor cycle performance, but the advantage is that it is low in price and has wide commercial applications; artificial graphite refers to graphite materials that are artificially prepared or screened, and the particle diameter size is basically consistent or the particle diameter distribution is narrower than natural graphite, so it has better compatibility with electrolytes and better performance, but it is more expensive and is commonly used in the field of high-performance lithium-ion secondary batteries such as high-end new energy vehicles; hard carbon refers to carbon materials that are difficult to graphitize even at temperatures above 2500°C, and its interior is a highly disordered carbon layer structure with an open void structure. All three can be purchased directly on the market.
[0019] Furthermore, the active material of the negative electrode includes at least hard carbon, and the mass content of the hard carbon is 0.1-100%. Preferably, the mass content of the hard carbon in the active material of the negative electrode is 1-50%; more preferably, the mass content of the hard carbon in the active material of the negative electrode is 5-20%.
[0020] The active material of the negative electrode contains hard carbon, which can significantly improve the diffusion capacity of lithium ions in the negative electrode and has excellent reaction kinetics. At the same time, the electrolyte of the present invention has good compatibility with the negative electrode material, which helps the electrolyte to form a stable and transparent liquid-solid interface during the first charge and discharge process of the battery, thereby improving the fast charging performance of the battery.
[0021] Further research found that the size of the diffusion impedance is mainly determined by the state of the solid phase material in the lithium-ion secondary battery. Although its distribution is distributed throughout the entire frequency domain, its main components are distributed in the low-frequency region (1-0.01Hz frequency domain). Therefore, the ratio of the AC impedance in the low-frequency region (1-0.01Hz frequency domain) to the AC impedance in the full frequency domain (10000-0.01Hz) is an important means to measure the diffusion impedance in the overall battery internal impedance, and is also an important indicator for measuring the battery fast charging performance.
[0022] Through the interaction of the pyrosulfate boron trifluoride composite lithium salt and the specific negative electrode active material of the present invention, the AC impedance of the lithium ion secondary battery in the frequency domain of 1 to 0.01 Hz accounts for 40 to 80% of the AC impedance in the frequency domain of 10000 to 0.01 Hz. Further, the AC impedance of the lithium ion secondary battery in the frequency domain of 1 to 0.01 Hz accounts for 60 to 70% of the AC impedance in the frequency domain of 10000 to 0.01 Hz.
[0023] Specifically, the AC impedance is measured at 0-45°C and 20%-80% state of charge of the battery. In a specific embodiment, the AC impedance values in different frequency domains can be measured at room temperature and about 50% state of charge of the battery.
[0024] In addition, the positive electrode, negative electrode, diaphragm of the battery, and the liquid-solid interface formed by the interaction between the electrolyte and the positive and negative electrodes will all affect the charge transfer impedance. Among them, the effect of the diaphragm is relatively small, so the present invention can use the diaphragm in common lithium-ion secondary batteries. Preferably, the diaphragm is selected from at least one of polyolefin diaphragms, polyester diaphragms, cellulose diaphragms, and polyimide diaphragms, and the diaphragm can be further processed using ceramic coating technology. The present invention uses the positive electrode material in common lithium-ion secondary batteries. Although the positive electrode material has a certain effect on the charge transfer impedance, in order to improve the battery energy density, the present invention adopts a high-voltage battery system, so there are certain limitations in the selection of positive electrode materials. Preferably, the active material of the positive electrode is selected from at least one of lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium cobalt oxide, lithium nickel oxide, layered lithium manganese oxide, spinel lithium manganese oxide, and lithium nickel manganese oxide materials.
[0025] Generally, electrolyte additives and the liquid-solid interface formed by the additives and the negative electrode have a great influence on the size of the charge transfer impedance of lithium-ion secondary batteries. The process of lithium ions migrating from the liquid-solid interface to the solid phase of the negative electrode material is the main component of the charge transfer impedance. The AC impedance generated by it is partially distributed in the low-frequency region of 1 to 0.1 Hz, and partially overlaps with the diffusion impedance. Through the decoupling data mentioned in the present invention, it is found that within the above-mentioned test temperature and charge state range of the present invention, the charge transfer impedance accounts for 20 to 40% of the AC impedance in the full frequency domain of 10000 to 0.01 Hz.
[0026] Due to the different preparation process parameters of the novel composite lithium salt, the novel composite lithium salt also includes at least one of the compounds represented by the following formulas (I-2), (I-3), (I-4), (I-5), and (I-6):
[0027]
[0028]
[0029]
[0030] The novel composite lithium salt contains at least 80.0wt% of the pyrosulfate boron trifluoride composite lithium salt having the structure shown in formula (I-1). Preferably, the novel composite lithium salt contains 80.0-95.0wt% of the pyrosulfate boron trifluoride composite lithium salt having the structure shown in formula (I-1), and the rest is at least one of compounds (I-2), (I-3), (I-4), (I-5) or (I-6).
[0031] According to the above-mentioned high-voltage fast-charging lithium-ion secondary battery, the additive also includes a basic additive, and the basic additive is selected from at least one of vinylene carbonate, fluoroethylene carbonate, vinyl vinyl carbonate, tris(trimethylsilyl) phosphate, 1,3-propane sultone, 1,3-propylene sultone, vinyl sulfate, lithium difluorophosphate, lithium bis(fluorosulfonyl)imide, succinic anhydride, adiponitrile, cyclohexylbenzene, lithium difluorobis(oxalate)phosphate or lithium difluorobis(oxalate)borate, and the mass percentage of any one of the basic additives in the electrolyte is 0.1 to 5.0 wt%, preferably 0.1 to 2.0 wt%.
[0032] In a specific embodiment, the basic additives are lithium difluorooxalatoborate (LiDFOB) and lithium difluorophosphate (LiDFP), each accounting for 0.1% to 2.0% of the total mass of the electrolyte. Through their interaction with the new composite lithium salt and the negative electrode active material, the fast charging performance and low temperature performance of the lithium-ion secondary battery can be further improved.
[0033] In another embodiment, the basic additives are fluoroethylene carbonate (FEC), diethylene sulfate (DTD) and tris(trimethylsilyl) phosphate (TMSP), each accounting for 0.1% to 2.0% of the total mass of the electrolyte. Through their interaction with the new composite lithium salt and the negative electrode active material, the fast charging performance and low temperature performance of the lithium-ion secondary battery can be further improved.
[0034] According to the above-mentioned high-voltage fast-charging lithium-ion secondary battery, the main lithium salt is selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium hexafluoroarsenate, lithium perchlorate, lithium bis(oxalatoborate), lithium difluorooxalatoborate, lithium bis(fluorosulfonyl imide), lithium bis(trifluoromethylsulfonyl imide), lithium tetrafluorooxalate phosphate, lithium trioxalate phosphate or lithium difluorobis(oxalatophosphate), and its molar concentration is 0.1 to 4.0 mol / L.
[0035] According to the above-mentioned high voltage fast-charge lithium-ion secondary battery, the non-aqueous solvent is selected from at least one of C3-C6 carbonate compounds, C3-C8 carboxylate compounds, sulfone compounds, ether compounds, and nitrile compounds;
[0036] Preferably, the C3-C6 carbonate compounds are selected from at least one of ethylene carbonate, propylene carbonate, butylene carbonate, dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, and methyl-2,2,2-trifluoroethyl; the C3-C8 carboxylate compounds are selected from at least one of γ-butyrolactone, methyl acetate, methyl propionate, methyl butyrate, ethyl acetate, ethyl propionate, ethyl butyrate, propyl acetate, propyl propionate, and 2,2-difluoroethyl acetate; the sulfone compounds are selected from at least one of cyclobutane sulfoxide, dimethyl sulfoxide, dimethyl sulfone, and diethyl sulfone; the ether compounds are selected from at least one of triethylene glycol dimethyl ether and / or tetraethylene glycol dimethyl ether; the nitrile compounds are selected from at least one of acetonitrile, succinonitrile, adiponitrile, 1,3,6-hexanetrinitrile, p-fluorobenzonitrile, and 1,2-bis(cyanoethoxy)ethane.
[0037] Preferably, the non-aqueous solvent is selected from a mixture of at least two of ethylene carbonate, propylene carbonate, dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, γ-butyrolactone, ethyl acetate, ethyl propionate, propyl propionate, succinonitrile, adiponitrile, and 1,3,6-hexanetrinitrile.
[0038] According to the above-mentioned high voltage fast charging lithium ion secondary battery, the negative electrode also includes auxiliary materials such as a current collector, a conductive agent, and a binder. Since the selection of the auxiliary materials has no obvious effect on the interaction between the electrolyte and the negative electrode mentioned in the present invention, the present invention has no limitation on the type of the auxiliary materials, and any known auxiliary materials can be used.
[0039] The active material of the positive electrode of the present invention can be a common positive electrode material of a lithium-ion secondary battery. Preferably, the active material of the positive electrode is selected from at least one of lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium cobalt oxide, lithium nickel oxide, layered lithium manganese oxide, spinel lithium manganese oxide, and lithium nickel manganese oxide. Further preferably, the active material of the positive electrode is selected from at least one of lithium nickel cobalt manganese oxide, lithium cobalt oxide, or lithium nickel oxide.
[0040] The high-voltage fast-charging lithium-ion secondary battery of the present invention has excellent low-temperature fast-charging performance, and the constant-current charging ratio at a charging rate of 1 to 6C and a cut-off working voltage of 4.2 to 5.0V is ≥75%; further, the constant-current charging ratio of the lithium-ion secondary battery at a charging rate of 2 to 4C and a cut-off working voltage of 4.25 to 4.45V is ≥90%.
[0041] Compared with the prior art, the present invention has the following beneficial effects:
[0042] 1. The present invention adopts a new type of composite lithium salt and a specific negative electrode to strengthen the interaction between the electrolyte and the negative electrode, solves the problem of excessively high solid phase impedance formed by the reaction of the electrolyte, the negative electrode, and the electrolyte and the negative electrode, thereby improving the fast charging performance and low temperature performance of the lithium-ion secondary battery.
[0043] 2. The present invention uses the relaxation time distribution function to decouple and distinguish the various components and their sizes in the internal impedance of the lithium-ion secondary battery, and verifies that only when and when the electrolyte and negative electrode of the present invention are used at the same time, the prepared lithium secondary battery can simultaneously have the effect of reducing the charge transfer impedance and reducing the diffusion impedance. Although the mechanism of how the electrolyte and negative electrode affect the charge transfer impedance and diffusion impedance is not clear and controversial, it is speculated through the analysis of the experimental results that the new composite lithium salt and the specific negative electrode of the present invention work synergistically during the battery preparation process to form a stable and ion-permeable electrolyte-negative electrode channel, thereby improving the electrochemical performance of the lithium-ion secondary battery. DETAILED DESCRIPTION
[0044] The present invention is further described below in conjunction with specific embodiments, but the present invention is not limited to these specific embodiments. Those skilled in the art should recognize that the present invention covers all possible alternatives, improvements and equivalents within the scope of the claims.
[0045] In the embodiments and comparative examples of the present invention, the types of novel composite lithium salts include the following:
[0046] Composite lithium salt A1: containing 95wt% of compound I-1 and 5wt% of compound I-2;
[0047] Composite lithium salt A2: contains 90 wt% of compound I-1, 6 wt% of compound I-2 and 4 wt% of compound I-3.
[0048] In the examples and comparative examples of the present invention, natural graphite, artificial graphite, hard carbon, silicon, and silicon dioxide were all purchased from Ningbo Shanshan Co., Ltd.
[0049] Example 1
[0050] This embodiment provides a method for preparing a lithium-ion secondary battery, which specifically includes the following steps:
[0051] Preparation of positive electrode
[0052] The positive electrode active material lithium nickel cobalt manganese oxide LiNi was mixed in a mass ratio of 93:4:3 0.7 Co 0.2 Mn 0.1 O2, conductive carbon black Super-P and binder polyvinylidene fluoride (PVDF), and then disperse them in N-methyl-2-pyrrolidone (NMP) to obtain positive electrode slurry. The slurry is evenly coated on both sides of the aluminum foil current collector, dried, rolled and vacuum dried, and welded with aluminum lead wires using an ultrasonic welder to obtain the positive electrode plate.
[0053] Preparation of negative plate
[0054] The negative electrode active material, conductive carbon black, binder styrene butadiene rubber (SBR) and carboxymethyl cellulose (CMC) were mixed in a mass ratio of 92:2:3:3, and then dispersed in deionized water to obtain a negative electrode slurry. The slurry was coated on both sides of the copper foil current collector, dried, rolled and vacuum dried, and a nickel lead wire was welded with an ultrasonic welder to obtain a negative electrode plate. Among them, the negative electrode active material was selected to have a specific surface area of 20m 2 / g of hard carbon.
[0055] Preparation of battery cells
[0056] A polyethylene microporous membrane with a thickness of 20 μm was placed between the positive plate and the negative plate as a separator, and then the sandwich structure consisting of the positive plate, the negative plate and the separator was wound, and after the tabs were drawn out, it was encapsulated in an aluminum-plastic film to obtain a soft-pack lithium-ion battery cell with a capacity of 1000 mAh to be filled with liquid.
[0057] Preparation of electrolyte
[0058] Ethylene carbonate (EC), diethyl carbonate (DEC) and ethyl methyl carbonate (EMC) were mixed at a mass ratio of EC:DEC:EMC=3:2:5, and then lithium hexafluorophosphate (LiPF6) and lithium bis(fluorosulfonyl)imide (LiFSI) were added to a molar concentration of 0.75 mol / L and 0.25 mol / L, respectively, to form a basic electrolyte. Then, 5.0% of the composite lithium salt A1 was added based on the total mass of the electrolyte.
[0059] Battery filling and formation
[0060] In a glove box with a moisture content of less than 10 ppm, the electrolyte prepared in this embodiment is injected into the battery cell, and the amount of electrolyte is to ensure that the gaps in the battery cell are filled. Then the formation is carried out according to the following steps: 0.01C constant current charging for 30 minutes, 0.02C constant current charging for 60 minutes, 0.05C constant current charging for 90 minutes, 0.1C constant current charging for 240 minutes, then leaving it for 1 hour and then shaping and sealing it, and then further charging it with a constant current of 0.2C to 4.40V, leaving it at room temperature for 24 hours, and then discharging it with a constant current of 0.2C to 3.0V.
[0061] On the basis of Example 1, the composite lithium salt and its content in the electrolyte, as well as the negative electrode active material and its content were changed, and other operations remained unchanged. A lithium ion secondary battery was prepared according to the electrolyte and negative electrode active material formula table in Table 1 below:
[0062] Table 1 Electrolyte and negative electrode active material formula
[0063]
[0064]
[0065] On the basis of Example 6, the electrolyte formula was changed, the negative electrode active material and its content remained unchanged, and other operations remained unchanged. The lithium ion secondary battery was prepared according to the electrolyte formula table in Table 2 below:
[0066] Table 2 Electrolyte formula
[0067]
[0068] 2. Electrochemical performance test
[0069] The above-mentioned lithium secondary battery is tested for various properties, including:
[0070] (1) AC impedance test:
[0071] This test is carried out at room temperature 25℃. The secondary battery is first charged to 50% SOC state, and an electrochemical workstation with electrochemical impedance spectroscopy test function is used to perform AC impedance test on the secondary battery. The initial frequency of the test is 10000Hz, the cut-off frequency is 0.01Hz, the disturbance voltage is ±0.01V, and the test points are not less than 60. The impedance data Z at each test frequency is obtained. n (n is the test frequency), and calculate the ratio c% of 1~0.01Hz AC impedance to 10000~0.01Hz AC impedance according to the following formula:
[0072] c%=(Z 0.01 -Z1) / (Z 0.01 -Z 10000 )×100%;
[0073] This ratio mainly reflects the situation where the diffusion impedance accounts for the battery impedance, and also includes the situation where part of the charge transfer impedance accounts for the battery impedance.
[0074] (2) Low temperature performance test:
[0075] ① Low temperature discharge capacity: Charge to 4.45V at 1C constant current at room temperature (25℃), and charge at constant voltage until the current drops to 0.05C, then discharge to 2.8V at 1C constant current, and record the room temperature discharge capacity C1. Repeat the above charging steps to 4.45V, then reduce the ambient temperature to -20℃, and place the battery at ambient temperature for 5 hours to achieve the purpose of cooling the battery. Then discharge to 2.5V at 0.5C constant current, record the discharge capacity C2, and the capacity retention rate R1:
[0076] R1=C2 / C1*100%.
[0077] ② Low temperature DCIR impedance: Fast charging performance test: At room temperature (25°C), the battery is charged to 50% SOC with a current of 0.2C, and then the ambient temperature is reduced to -20°C, and the battery is placed at ambient temperature for 5 hours to achieve the purpose of cooling the battery. Then, it is discharged at a constant current of 1C current I1 for 30s, and the voltage value V1 of the last 1s and the voltage value V2 of the 30s of discharge are recorded, and the low temperature DCIR impedance R2 is calculated according to the following formula:
[0078] R2 = (V1-V2) / I1.
[0079] (3) Rate charging performance test
[0080] At room temperature (25°C), the battery is charged at a constant current rate of 4C to a charging cut-off voltage of 4.45V, and then charged at a constant voltage until the current drops to 0.1C. The total charging capacity C3 and the constant current charging capacity C4 are recorded, and the battery constant current charging ratio R3 is calculated as follows:
[0081] R3=C4 / C3×100%.
[0082] The specific test results are shown in Table 3 below:
[0083] Table 3 Electrochemical test results
[0084]
[0085] By comparing Examples 1 to 2 and Comparative Examples 1 to 2 in Table 3 above, it can be seen that on the basis of using a negative electrode material with a specific specific surface area in a secondary battery, it is necessary to simultaneously use an electrolyte containing 0.02 to 5.0 wt % of a new composite lithium salt to obtain the interaction between the specific negative electrode and the electrolyte, thereby reducing the diffusion impedance ratio and charge transfer impedance ratio of the battery, and improving the fast charging performance and low temperature performance of the battery at high voltage.
[0086] By comparing Example 6 and Comparative Example 5 in Table 3 above, it can be seen that the fast charging performance and low temperature performance of the secondary battery can be improved only when and only when the lithium salt additive used is the composite lithium salt additive proposed in the present invention.
[0087] Comparison of Examples 1 to 4 and Comparative Examples 3 to 4 in Table 3 above shows that, on the basis of using a specific electrolyte additive in a secondary battery, a specific surface area of 0.1 to 20.0 m 2 / g of negative electrode active material can play a specific role in the interaction between the negative electrode and the electrolyte, thereby reducing the proportion of diffusion impedance and charge transfer impedance of the battery, and improving the fast charging performance and low temperature performance of the battery under high voltage. If the specific surface area is too small, there will be too few active sites on the negative electrode active material, which is not conducive to the occurrence of negative electrode-electrolyte interaction; if the specific surface area is too large, there will not be enough new composite lithium salts to participate in the negative electrode-electrolyte interface interaction, thus affecting the stability of the interface.
[0088] Comparing Examples 1 to 4 or Examples 10 to 12 in Table 3 above, it can be seen that when the usage of the novel composite lithium salt is further reduced to 0.1 to 2.0 wt %, the fast charging performance and low temperature performance of the secondary battery can be further improved.
[0089] Comparing Examples 1 to 4, or Examples 10, 13 to 14 in Table 3 above, it can be seen that when the specific surface area of the negative electrode active material is further reduced to 0.5 to 10.0 m 2 / g, the fast charging performance and low temperature performance of the secondary battery can be further improved.
[0090] In the present invention, the new composite lithium salt and the negative electrode active material interact with each other, so the usage of the new composite lithium salt and the specific surface area of the negative electrode active material affect each other. When the specific surface area of the negative electrode active material changes within the limit range of the present invention, the usage of the corresponding new composite lithium salt also needs to change within the limit range of the present invention to match the best performance effect.
[0091] By comparing Example 10 and Comparative Examples 5 to 6 in Table 3 above, it can be seen that when using negative electrode materials of a specific type and specific surface area, if the amount of the new composite lithium salt added is too small, it is not easy to form a dense and transparent interfacial phase, so that other lithium salts and / or solvents in the electrolyte participate in the interfacial phase film-forming reaction, increase the interfacial impedance, and are not conducive to fast charging performance and low temperature performance; if the amount of the new composite lithium salt added is too much, it itself is easy to form an overly dense interfacial phase during the battery manufacturing process, which is not conducive to the transmission of lithium ions, and is also not conducive to fast charging performance and low temperature performance.
[0092] By comparing Examples 5 to 9 and Comparative Examples 15 to 18 in Table 3 above, it can be seen that when hard carbon is used as one of the active negative electrode materials, it helps to further improve the ion conductivity of the negative electrode and produce a more stable and transparent lithium ion transmission channel with the new composite lithium salt, thereby further improving the fast charging performance and low temperature performance of the battery.
[0093] By comparing Example 6 and Examples 19 to 21 in Table 3 above, it can be seen that adding 0.1% to 2.0 wt % of other lithium salts of different types to the basic electrolyte can help further improve the fast charging performance and low temperature performance of the battery.
[0094] By comparing Example 6 and Examples 22 to 23 in Table 3 above, it can be seen that adding 0.1% to 2.0 wt % of different types of basic additives to the basic electrolyte can help further improve the fast charging performance and low temperature performance of the battery.
Claims
1. A high voltage fast charge lithium ion secondary battery, comprising a positive electrode, a negative electrode, a separator and an electrolyte, wherein the electrolyte comprises a main lithium salt, a non-aqueous solvent and an additive, characterized in that: The additives include: A novel composite lithium salt, wherein the novel composite lithium salt comprises at least a pyrosulfate boron trifluoride composite lithium salt having a structure shown in the following formula (I-1): The novel composite lithium salt accounts for 0.02-5.0wt% of the total mass of the electrolyte; Furthermore, the negative electrode comprises: An active material capable of reversibly absorbing and releasing lithium ions, wherein the specific surface area of the active material is 0.1 to 20.0 m 2 / g.
2. The high voltage fast charging lithium ion secondary battery according to claim 1, characterized in that: The specific surface area of the active material is 0.5 to 10.0 m 2 / g.
3. The high voltage fast charge lithium ion secondary battery according to claim 1, characterized in that: The active material of the negative electrode is selected from carbon materials and / or silicon materials; the carbon material is selected from at least one of natural graphite, artificial graphite, and hard carbon, and the silicon material is selected from silicon and / or silicon oxide.
4. The high voltage fast charge lithium ion secondary battery according to claim 3, characterized in that: The active material of the negative electrode at least includes hard carbon, and the mass content of the hard carbon is 0.1-100%.
5. The high voltage fast charge lithium ion secondary battery according to claim 4, characterized in that: In the active material of the negative electrode, the mass content of hard carbon is 5 to 20%.
6. The high voltage fast charge lithium ion secondary battery according to claim 1, characterized in that: The novel composite lithium salt accounts for 0.1-2.0 wt% of the total mass of the electrolyte.
7. The high voltage fast charge lithium ion secondary battery according to any one of claims 1 to 6, characterized in that: The AC impedance of the lithium ion secondary battery in the frequency domain of 1 to 0.01 Hz accounts for 40 to 80% of the AC impedance in the frequency domain of 10000 to 0.01 Hz.
8. The high voltage fast charge lithium ion secondary battery according to claim 7, characterized in that: The AC impedance of the lithium ion secondary battery in the frequency domain of 1 to 0.01 Hz accounts for 60 to 70% of the AC impedance in the frequency domain of 10000 to 0.01 Hz.
9. The high voltage fast charge lithium ion secondary battery according to claim 1, characterized in that: The novel composite lithium salt also includes at least one of the compounds represented by the following formulas (I-2), (I-3), (I-4), (I-5), and (I-6): The novel composite lithium salt contains at least 80.0 wt % of the pyrosulfate boron trifluoride composite lithium salt having the structure shown in formula (I-1).
10. The high voltage fast charge lithium ion secondary battery according to claim 9, characterized in that: The novel composite lithium salt contains 80.0 to 95.0 wt % of the pyrosulfate boron trifluoride composite lithium salt having the structure shown in the formula (I-1), and the rest is at least one of the compounds (I-2), (I-3), (I-4), (I-5) or (I-6).
11. The high voltage fast charge lithium ion secondary battery according to claim 1, characterized in that: The additives also include basic additives, which are selected from at least one of vinylene carbonate, fluoroethylene carbonate, vinyl vinyl carbonate, tris(trimethylsilyl) phosphate, 1,3-propane sultone, 1,3-propylene sultone, vinyl sulfate, lithium difluorophosphate, lithium bis(fluorosulfonyl)imide, succinic anhydride, adiponitrile, cyclohexylbenzene, lithium difluorobis(oxalate)phosphate or lithium difluorobis(oxalate)borate, and the mass percentage of any one of the basic additives in the electrolyte is 0.1 to 5.0 wt%.
12. The high voltage fast charging lithium ion secondary battery according to claim 1, characterized in that: The main lithium salt is selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium hexafluoroarsenate, lithium perchlorate, lithium bis(oxalatoborate), lithium difluorooxalatoborate, lithium bis(fluorosulfonyl imide), lithium bis(trifluoromethylsulfonyl imide), lithium tetrafluorooxalate phosphate, lithium trioxalate phosphate or lithium difluorobis(oxalatophosphate), and its molar concentration is 0.1-4.0 mol / L.
13. The high voltage fast charging lithium ion secondary battery according to claim 1, characterized in that: The non-aqueous solvent is selected from at least one of C3-C6 carbonate compounds, C3-C8 carboxylic acid ester compounds, sulfone compounds, ether compounds, and nitrile compounds; The C3-C6 carbonate compounds are selected from at least one of ethylene carbonate, propylene carbonate, butylene carbonate, dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, and methyl-2,2,2-trifluoroethyl; the C3-C8 carboxylic acid ester compounds are selected from at least one of γ-butyrolactone, methyl acetate, methyl propionate, methyl butyrate, ethyl acetate, ethyl propionate, ethyl butyrate, propyl acetate, propyl propionate, and 2,2-difluoroethyl acetate; the sulfone compounds are selected from at least one of cyclobutane sulfone, dimethyl sulfoxide, dimethyl sulfone, and diethyl sulfone; the ether compounds are selected from at least one of triethylene glycol dimethyl ether and / or tetraethylene glycol dimethyl ether; the nitrile compounds are selected from at least one of acetonitrile, succinonitrile, adiponitrile, 1,3,6-hexanetrinitrile, p-fluorobenzonitrile, and 1,2-bis(cyanoethoxy)ethane.
14. The high voltage fast charge lithium ion secondary battery according to claim 1, characterized in that: The active material of the positive electrode is selected from at least one of lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium cobalt oxide, lithium nickel oxide, layered lithium manganese oxide, spinel lithium manganese oxide or lithium nickel manganese oxide.
15. The high voltage fast charge lithium ion secondary battery according to any one of claims 1 to 14, characterized in that: The lithium ion secondary battery has a constant current charging ratio of ≥75% when it is charged at a constant current and constant voltage at a charging rate of 1-6C and a cut-off working voltage of 4.2-5.0V.
16. The high voltage fast charge lithium ion secondary battery according to claim 15, characterized in that: The constant current charging ratio of the lithium ion secondary battery at a charging rate of 2 to 4C and a cut-off working voltage of 4.25 to 4.45V is ≥90%.
Citation Information
Patent Citations
Non-aqueous electrolyte of high-voltage lithium ion battery
CN107799822A
Lithium-ion battery electrolyte and lithium-ion battery containing same
CN111029653A
Lithium ion battery electrolyte and lithium ion battery containing same
CN111430796A
Non-aqueous electrolyte containing sulfur-containing lithium salt derivative additive and lithium ion battery
CN112349951A
Difluoro cyclic sulfuric acid and boric acid lithium salt, electrolyte containing difluoro cyclic sulfuric acid and boric acid lithium salt and lithium ion battery
CN117510528A